1987
DOI: 10.1136/gut.28.8.924
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cancer at multiple sites after gastric surgery for peptic ulcer.

Abstract: SUMMARY Of 5018 patients who had undergone gastric surgery at St James Hospital, Balham, at least 25 years ago, death certificates have been received for 2768, whilst 1746 patients are still alive and are flagged (Office of Populations, Censuses and Surveys (OPCS) will notify us of their death and its cause) and only 504 could not be traced. Mortality from cancers of various organs has been determined using a 'years at risk' calculation in five year bands. There was no increase in mortality risk from any cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 9 publications
5
53
0
1
Order By: Relevance
“…The literature review by Fletcher & Clarke (1968) throws doubt on such an association in these patients; however a recent study by Mazzanti et al (1986) observed a prevalence of gallstones of 36% in gastric surgery patients. Alternatively, in a previous publication (Caygill et al, 1987) we have noted that the increased risk in gastric surgery patients of cancer at sites additional to the stomach was consistent with a causal role for circulating organotropic carcinogens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature review by Fletcher & Clarke (1968) throws doubt on such an association in these patients; however a recent study by Mazzanti et al (1986) observed a prevalence of gallstones of 36% in gastric surgery patients. Alternatively, in a previous publication (Caygill et al, 1987) we have noted that the increased risk in gastric surgery patients of cancer at sites additional to the stomach was consistent with a causal role for circulating organotropic carcinogens.…”
Section: Resultsmentioning
confidence: 99%
“…The study population was 4,466 patients treated surgically for peptic ulcer at St James Hospital, Balham between 1940 and1960 and has been reported in detail elsewhere , Caygill et al (1986, Caygill et al ( , 1987 at risk' in 5 year bands from the age at operation. The probability levels were calculated using the Poisson approximation to the binomial distribution.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 16 previous studies that have examined gastrectomy as a risk factor for pancreatic cancer, ten reported a positive association (McLeanRoss et al, 1982;Mack et al, 1986;Caygill et al, 1987;Offerhaus et al, 1987;Mills et al, 1988;Farrow and Davis, 1990;Tersmette et al, 1990;Eide et al, 1991;Mooller and Toftgaard, 1991;Bueno de Mesquita et al, 1992), while six studies in addition to ours found no association (Wynder et al, 1973;Maringhini et al, 1987;La Vecchia et al, 1990;Jain et al, 1991;Kalapothaki et al, 1993;Gullo et al, 1996). Of only four studies that examined history of ulcer in relation to pancreatic cancer risk, none found an association in accord with our findings (Mack et al, 1986;La Vecchia et al, 1990;Jain et al, 1991;Bueno de Mesquita et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiologic investigations on the issue are limited to patients who had undergone gastric surgery (2,3).…”
mentioning
confidence: 99%